The formation of a creative imagination of junior pupils at the lessons of literary reading by means of innovation technologies - Білоконна, Ніна Іванівна (Pedagogy of Higher and Secondary Education, 2019)
Belokonnaia N. I. The formation of a creative imagination of junior pupils at the lessons of literary reading by means of innovation technologies. The article dealth with the methods of organization and carrying out the lessons of literary reading at a primary school. The author analyzes traditional and other methodical techniques promoting the organization of pupils’ team-work at the reading lesson; considers modern educational technologies as the most effective for formation of a creative imagination of junior pupils in the process of studying literary works.